Network Performance Analysis Using Optical-to-RJ11 Converters in Point-to-Point Communication - Nurhansyah, Haidar Achmad; Isnomo, Yoyok Heru Prasetyo; Waluyo, Waluyo; Setiadi, Chandrasena (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Currently, fiber optic cable is the most sophisticated transmission medium and is starting to be widely used for data transmission. However, like any other transmission medium, fiber optic cables also produce attenuation or loss. This study analyzes network performance using 2 converters that will be connected to RJ11 telephones and single mode optical cables with predetermined specifications. Analysis on this network is carried out to determine the results of the attenuation value and sound quality on the fiber optic network. The data collection technique that was carried out began with designing the research materials. The materials used are single mode fiber optic cables, RJ11, converters, telephone servers, and telephones as information senders and receivers. Measuring tools used are Sound Spectrum analyzer and OPM. Conducted research by changing the bending of fiber optic cable in order to determine the performance of the communication system. The results are loss values as well as sound output on the fiber optic cable . The quality of network performance based on the measured bending loss values has different results. The smallest loss occurs at 5 cm bending which is -11.46 dBm and the largest at 0.5 cm bending is -50.00 dBm. The bending value used also affects the quality of the sound emitted on the telephone, where at the largest bending, which is 5 cm, the sound output power value is 77.475 dB. Meanwhile, when the smallest bending is 0.5 cm, the resulting value is only around 49.7 dB